2015
DOI: 10.4314/ahs.v15i3.41
|View full text |Cite
|
Sign up to set email alerts
|

The scourge of head injury among commercial motorcycle riders in Kampala; a preventable clinical and public health menace

Abstract: Background: Trauma is an increasingly important cause of disease globally. Half of this trauma is from road traffic injuries with motorcycles contributing 21-58%. Low protective gear use, lack of regulation and weak traffic law enforcement contribute to unsafe nature of commercial motorcycles also known as "boda boda" in Uganda. Objectives: To determine the prevalence of protective gear use, the occurrence of head injury and the relationship between the two among commercial motorcycle riders in Kampala. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
39
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 14 publications
(21 reference statements)
10
39
3
Order By: Relevance
“…Some road users are vulnerable to RTIs largely because of their own reckless actions or inactions. Pedestrians and passengers, however, are commonly much more vulnerable to becoming innocent victims of RTIs compared to other road users [7–10, 3638]. The riders and passengers of the 2 wheeler Boda-bodas (commercial motorcycles) have also increasingly become vulnerable to RTIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some road users are vulnerable to RTIs largely because of their own reckless actions or inactions. Pedestrians and passengers, however, are commonly much more vulnerable to becoming innocent victims of RTIs compared to other road users [7–10, 3638]. The riders and passengers of the 2 wheeler Boda-bodas (commercial motorcycles) have also increasingly become vulnerable to RTIs.…”
Section: Discussionmentioning
confidence: 99%
“…Of recent, the numbers of Boda-bodas have been exponentially rising to the point that it now predominates the public transport system of the KMA and Uganda [3, 24, 36, 38, 39]. They are mainly manned by the youths who seek to make-ends-meet.…”
Section: Discussionmentioning
confidence: 99%
“…Under Uganda's Traffic and Road Safety (Motorcycles) Regulations, all motorcyclists and their passengers have been required, since 2004, to wear crash helmets while operating the vehicle [34]. However, as multiple studies have shown, adherence to helmet use is far from ideal [5,14,25]. This pattern of nonadherence is especially worrisome, given the increasing involvement of boda bodas in RTIs.…”
Section: Motorcycle Helmet Usage In Ugandamentioning
confidence: 99%
“…Unfortunately, there is poor helmet usage among boda boda drivers. Various studies of Ugandan emergency departments have shown only 18.6% to 22% of motorcyclists wore helmets [5,14]. Given the serious cost of RTIs and the relatively low cost of helmets, this discrepancy reflects an important area that public health should address.…”
Section: Introductionmentioning
confidence: 99%
“…One [22]. But while this problem affects all of Kampala's residents equally, SafeBoda's appbased approach, borrowed from Uber, is unlikely to attract many customers save development workers or those from very elite backgrounds.…”
Section: Learning the Wrong Lessonsmentioning
confidence: 99%